Becoming Aware of Inner Self-Critique and Kinder Toward Self: A Qualitative Study of Experiences of Outcome After a Brief Self-Compassion Intervention for University Level Students - Binder, Per-Einar; Dundas, Ingrid; Stige, Signe Hjelen; Hjeltnes, Aslak; Woodfin, Vivian; Moltu, Christian (Frontiers in Psychology, 2019)
This qualitative study investigated ways students participating in a three-session self-compassion course became, but found it challenging to become, more compassionate towards themselves. Ninety-six participants completed an online questionnaire and 12 participants were interviewed. Thematic analysis of the written responses identified five themes as most frequent: 1) being more supportive and friendlier towards self, 2) being more aware of being too hard on oneself, 3) feeling less alone when having painful feelings, 4) having more acceptance of painful feelings, and 5) feeling more stable and peaceful . These themes were explored through phenomenological analysis of the interviews.